The World Bank Annual Report 2006, Volume 2. Management's Discussion and Analysis - World Bank (Washington, DC, 2012)
This World Bank Annual Report for FY2006 notes that the past year saw both progress and continued challenges in the global fight against poverty and inequality. The Report discusses the following topical highlights: Debt relief for the poorest countries; targeting development in Africa; addressing governance and anticorruption issues globally; improving partnerships with the international community; quick responses to potential avian flu outbreaks; and disaster relief. There were 112 IBRD projects totaling $14.1 billion. The top three sectors for lending were Law and Justice and Public Administration; Transportation; and Energy and Mining. As for IDA concessional lending, 167 projects totaled $9.5 billion. The top three Sectors were Law and Justice and Public Administration; Transportation; and Health and Other Social Services. Non-lending Activities comprises 307 technical assistance activities; and 601 economic and sector work products. There were 16 major evaluations by the Independent Evaluation Group reviewing the Bank's performance on a range of activities including country assistance, debt relief, development effectiveness, middle-income countries, post-disaster assistance, and trade. More than 150 publications were issued, including Global Development Finance 2006, Global Monitoring Report 2006, World Development Indicators 2006, and World Development Report 2006: Equity and Development. While country-led poverty reduction and national development strategies continued to be important mechanisms for defining country priorities and aid strategies, several additional issues moved to the forefront of the Bank's activities during fiscal 2006. These diverse issues included improving governance and accountability, implementing a new Multilateral Debt Relief Initiative, expanding initiatives undertaken within the 2005 Africa Action Plan, developing a framework for middle-income countries, supporting agriculture in the poorest countries, cooperating with other international organizations to combat avian flu, searching for new approaches to deal with climate change, and strengthening partnerships to put in place a monitoring plan for the March 2005 Paris Declaration on Aid Effectiveness. The Bank also responded to emergencies, including the October 2005 earthquake in northern Pakistan and the May 2006 earthquake in Indonesia.